Comparative risk of type 2 diabetes development between women with gestational diabetes and women with impaired glucose tolerance over two decades: a multiethnic prospective cohort in New Zealand - Hang Fu; Dahai Yu; Zheng Wang; Yamei Cai; Zhanzheng Zhao; David Simmons; Karen Pickering; John Baker; Gerhard Sundborn; Richard Cutfield; Brandon J Orr-Walker; Chengzeng Wang (BMJ Open Diabetes Research & Care, 2024)
Introduction To evaluate the long-term risk of developing type 2 diabetes (T2D) among women with a history of gestational diabetes mellitus (GDM) compared with those with impaired glucose tolerance (IGT).Research design and methods Using data from a primary care dataset linked with multiple health registries, this longitudinal study analyzed demographics, clinical data, and lifestyle factors of women diagnosed with GDM or IGT, assessing T2D incidence over 25 years, using Cox regression models.Results Women with GDM, especially those over 35 years of Māori ethnicity, or socioeconomic deprivation, exhibited an elevated risk of T2D compared with those with IGT. The first 5 years post partum emerged as a critical window for intervention.Conclusions This study underscores the importance of early, targeted post-GDM interventions to mitigate T2D risk. It highlights the necessity of personalized post-GDM interventions to reduce T2D incidence which consider age, ethnicity, and socioeconomic status to maximize effectiveness.